(untitled) (Tamaddun, 2025)
TikTok has become one of the most popular social media platforms among teenagers, offering a variety of content ranging from entertainment and challenges to light education. This phenomenon raises questions about how the content consumed and created by teenagers influences their behaviour and lifestyle. This study aims to analyse the influence of TikTok content on teenagers’ daily activities, social interactions, and identity expression. This study employs a qualitative case study approach to understand teenagers’ self-representation on TikTok at SMAN 2 Makassar, with subjects being active OSIS students who have TikTok accounts. Data was collected through content observation, semi-structured interviews, and literature studies, then analysed thematically and in terms of content to capture visual themes, texts, and social meanings. Data validity was ensured through triangulation, member checks, and rich descriptions, so that the research findings are reliable and provide an in-depth description of how teenagers express their identity, lifestyle, and social interactions. The results of the study show that entertainment, challenges, and light education are the types of content most consumed and created by teenagers. This content represents their lifestyle, including hobbies, fashion, daily habits, and social interactions, and serves as a means of expressing their identity and aspirations. The influence of TikTok content on adolescent behaviour is twofold; on the one hand, it can encourage creativity, positive social interaction, and identity formation, but on the other hand, it can cause social pressure, consumptive behaviour, and psychological effects due to social comparison. This study emphasises the importance of media literacy so that adolescents can use TikTok productively and safely.